Systematics of states of mental maladaptation in students - V. M. Sinayko; M. M. Khaustov (Kazimierz Wielki University, 2018)
The objective: to specify clinical, psychopathological and pathopsychological manifestations of psychological maladaptation in the students. A total clinical-anamnestic, clinical-psychopathological and psychodiagnostic examination was carried out for 412 students of the KhNMU with an average age of 19.5 ± 2.5 years, 147 men and 265 women. Based on the data of the analysis of the levels of maladaptation, we allocated three groups of students: Group 1 - low level of maladaptation - 46.0 ± 2.1% of the surveyed people, group 2 - moderate level of maladaptation 37.6 ± 2.1%, group 3 - high level of maladaptation 16.4 ± 1.6%. In the course of the work, the phenomenology of the mental state of students was conducted. Maladaptive conditions were determined by a decrease in mental health, exhaustion of attention, decreased productivity intellectual activity, irritability, hyperesthesia, anxiety, painful decline in mood, asthenia, low self-esteem, self-doubt, high levels of severity asthenic state and neuro-psychic tension.